Stigma of Former Drug Offenders: Islamic and Restorative Justice Perspectives in the Contemporary Era - Fatah Chotib Uddin; Sri Sulistyawati; Kartina Pakpahan; Roswita Sitompul (MILRev: Metro Islamic Law Review, 2025)
This study offers a sociological and normative analysis of the persistent stigmatisation of former drug offenders and its implications for the implementation of restorative justice and Islamic ethical values in the contemporary Indonesian context. Employing a qualitative approach through field research and literature review, the study investigates the socio-cultural dynamics, public perceptions, and institutional obstacles that hinder the effective reintegration of ex-offenders into society. The findings indicate that former drug offenders often face multilayered stigma—manifesting in social exclusion, limited employment opportunities, and distrust within their communities—which significantly undermines the objectives of restorative justice. These challenges prolong the cycle of marginalisation and contradict the restorative principles of reconciliation, rehabilitation, and social healing. Moreover, the study reveals a gap between legal-normative frameworks and community practices, where punitive attitudes prevail over rehabilitative intentions. From the perspective of Islamic ethics, values such as rahmah (compassion), tawbah (repentance), and islah (reconciliation) serve as essential moral foundations that advocate for the acceptance and reintegration of reformed individuals. These values emphasise the potential for personal transformation and the collective responsibility of society to facilitate restorative outcomes. This study recommends a holistic synergy between restorative justice mechanisms, Islamic ethical values, and public education initiatives to dismantle stigma, promote inclusivity, and foster a more humane justice system. The academic contribution of this research lies in its integrative framework that combines socio-legal theory with Islamic moral philosophy to critically assess the structural and cultural barriers to reintegration, offering a contextualised model for human-centred restorative justice in Muslim-majority societies.